Maternalism and new imperialism in Russia: “good mothers” for a militarizing state—expectations, implications, and resistances - Gradskova, Yulia (Frontiers in Sociology, 2023)
This article explores maternalism in Russia, in the context of the contemporary Russian authoritarian state. In particular, I analyze what implications maternalism has for women, mothers and families on the one hand, and how it is connected to the Russian state's new imperial ambitions on the other. I also explore how maternalism is challenged and employed by those resisting the state politics, including militarism.Historically, maternalism was used for analysis of the development of the welfare state in Europe and beyond, as well as for studying women's activism that contributed to significant changes in the states' welfare politics (Bock & Thane, 1991; Daly 2022, 314-315).Maternalism in European history could be seen as a "a progressive heterosexual maternal womanhood" (McRobbie, 2014, 120); according to Mary Daly, it could be explained as a recognition of the "existence of a uniquely feminine value system based on care and nurturing", and as the assumption that women are performing "a service to the state by raising citizen-workers" (Daly, 2022, 316). Gender historians of Latin America showed that speaking from the position of a mother was quite important for claiming both the right to be accepted as an equal citizen as well as the improvement of the maternity care, welfare and living conditions for mothers and children (Luna, 2003, 54-57; Piepper Mooney, 2013). Furthermore, maternalism was widely used in protests against state militarism, wars and military dictatorships, not least as a part of the campaign against the Vietnam war or crimes of Argentinian military dictatorship (Pieper Mooney, 2013; Luna, 2003, 57). However, maternalism was also widely used by several totalitarian regimes, including fascism (see Saraceno, 1991) and Stalinism (Nakachi, 2021). Maternalism was an important political instrument used by the state socialist discourse in order to show the superiority of the "socialist" welfare system over the "capitalist" one, and to make this system appear attractive to women from "developing" countries (Gradskova, 2021).